Effects of Temperature and Light Intensity on the Growth and Physiological and Biochemical Characteristics of Young Sporophyte of a Novel Saccharina japonica "Huangguan No.2" - Guiyang SONG; Zhourui LIANG; Xiaoping LU; Yanmin YUAN; Wenjun WANG (Progress in Fishery Sciences)
The study aimed to investigate the optimal light and temperature conditions, and physiological and biochemical mechanisms for the growth of young sporophytes (3–4 cm) of "Huangguan No.2". We conducted corresponding studies on the growth and physiological and biochemical conditions of young sporophytes under different light intensities and temperatures, including the relative growth rate (RGR), fluorescence parameter of chlorophyll, contents of pigments/proteins, reactive oxygen, antioxidants, and activity of antioxidant enzymes. The results showed that RGR was significantly affected by light, temperature, and their interaction. The degree of influence from large to small is temperature, light intensity and their interaction. They exhibited the highest RGR at 10–13 ℃ and 60–90 μmol photons/(m2·s), whereas the RGR of the high temperature (16 ℃ and 19 ℃) group was highest at 30 μmol photons/(m2·s). At the same temperature, the chlorophyll-a and carotenoid contents of young sporophytes decreased with increasing light intensity. Additionally, the SOD activities and ascorbic acid (AsA) contents tended to increase. Under the same light intensity, compared to 10–13 ℃, the contents of soluble protein decreased in the high temperature group; whereas the contents of MDA and H2O2 significantly increased. Additionally, the SOD, GSH-Px, and APX activities and antioxidant (AsA and carotenoids) contents were all higher. The maximum photochemical efficiency of photosystem Ⅱ (Fv/Fm) was significantly lower in the high temperature and high light [(120 μmol photons/(m2·s)] groups, indicating that the light energy conversion efficiency of the alga was reduced under high temperature and high light stress. In the high light group, the quantum yield of regulated non-photochemical energy loss in photosystem Ⅱ [Y(NPQ)] increased significantly and the initial slope (α) of the fast light curve decreased significantly. This suggests that the photoprotective system of young sporophytes of "Huangguan No.2" responded positively to the high light stress and reduced the absorption of light energy by lowering the efficiency of light energy utilization to reduce the photodamage. The activities of key antioxidant enzymes and the antioxidant contents in the high light and high temperature groups were significantly higher, indicating that the antioxidant systems of young sporophytes responded positively to high light and high temperature stresses to minimize the damage caused by reactive oxygen species. Under low light [10 μmol photons/(m2·s)] group, Fv/Fm, α, actual quantum yield of photosystem Ⅱ [Y(Ⅱ)], the chlorophyll-a contents significantly increased. This indicates that the light energy conversion efficiency and light energy utilization efficiency significantly increased in the low light environment, which led to an increase in the absorption of light energy. These results on the physiological and ecological adaptations of young sporophytes under the conditions of temperature and light intensity can provide a theoretical basis for further optimizing the light and temperature parameters of young sporophytes of "Huangguan No.2" during intermediate culture of young sporelings.